Theoretical and Experimental Studies on the Near‐Infrared Photoreaction Mechanism of a Silicon Phthalocyanine Photoimmunotherapy Dye: Photoinduced Hydrolysis by Radical Anion Generation. Issue 9 (25th May 2020) - Kobayashi, Masato; Harada, Mei; Takakura, Hideo; Ando, Kanta; Goto, Yuto; Tsuneda, Takao; Ogawa, Mikako; Taketsugu, Tetsuya
Abstract: Ligand release from IR700, a silicon phthalocyanine dye used in near‐infrared (NIR) photoimmunotherapy, initiates cancer cell death after NIR absorption, although its photochemical mechanism has remained unclear. This theoretical study reveals that the direct Si‐ligand dissociation by NIR light is difficult to activate because of the high dissociation energy even in excited states, i. e., >1.30 eV. Instead, irradiation generates the IR700 radical anion, leading to acid‐base reactions with nearby water molecules (i. e., calculated pK b for the radical anion is 7.7) to produce hydrophobic ligand‐released dyes. This suggests two possibilities: (1) water molecules participate in ligand release and (2) light is not required for Si–ligand dissociation as formation of the IR700 radical anion is sufficient. Experimental evidence confirmed possibility (1) by using 18 O‐labeled water as the solvent, while (2) is supported by the pH dependence of ligand exchange, providing a complete description of the Si‐ligand bond dissociation mechanism. Abstract : The computational and experimental studies demonstrated that the mechanism of action for near‐infrared (NIR) photoimmunotherapy using the key Si phthalocyanine dye, IR700, is a result of the formation of IR700 radical anion. The dissociation of the axial ligands from IR700 has been established as the initiation of cancer cell death, though understanding the mechanism to bring this about has remained elusive. The ligand dissociation proceeds by the hydrolysis of this radical anion, rather than any dissociative excited‐state channel.